2013
DOI: 10.1038/aps.2013.130
|View full text |Cite
|
Sign up to set email alerts
|

Cysteinyl leukotriene receptor 1 mediates LTD4-induced activation of mouse microglial cells in vitro

Abstract: Aim: To investigate the roles of cysteinyl leukotriene receptors CysLT 1 R and CysLT 2 R in leukotriene D 4 (LTD 4 )-induced activation of microglial cells in vitro. Methods: Mouse microglial cell line BV2 was transfected with pcDNA3.1(+)-hCysLT 1 R or pcDNA3.1(+)-hCysLT 2 R. The expression of relevant mRNAs and proteins in the cells was detected using RT-PCR and Western blotting, respectively. Phagocytosis was determined with flow cytometry analysis. The release of interleukin-1β (IL-1β) from the cells was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Whether this marked upregulation leads to a greater neutrophilia or is secondary to the recruitment of neutrophils is not clear, but the lack of comparable increases in lta4h expression suggests that the findings are not attributable simply to neutrophil recruitment. Additionally, reduced efferocytosis of neutrophils by macrophages is suggested by in vitro studies that have shown that cysLT 1 R antagonists inhibit phagocytic activity, whereas overexpression of cysLT 1 R enhances phagocytosis (48). In vivo, alveolar macrophages in CysLTr1 2/2 mice exhibit impaired phagocytic activity (49), and sPLA2-dependent cysLT generation partially mediates macrophage phagocytic activity in a model of immune erosive inflammatory arthritis (50).…”
Section: Discussionmentioning
confidence: 99%
“…Whether this marked upregulation leads to a greater neutrophilia or is secondary to the recruitment of neutrophils is not clear, but the lack of comparable increases in lta4h expression suggests that the findings are not attributable simply to neutrophil recruitment. Additionally, reduced efferocytosis of neutrophils by macrophages is suggested by in vitro studies that have shown that cysLT 1 R antagonists inhibit phagocytic activity, whereas overexpression of cysLT 1 R enhances phagocytosis (48). In vivo, alveolar macrophages in CysLTr1 2/2 mice exhibit impaired phagocytic activity (49), and sPLA2-dependent cysLT generation partially mediates macrophage phagocytic activity in a model of immune erosive inflammatory arthritis (50).…”
Section: Discussionmentioning
confidence: 99%
“…CysLTs act on at least two G protein-coupled receptors, CysLT1R and CysLT2R, which mediate various responses in the peripheral and central nervous systems [5]. In more recent years, focus has intensified on CysLT1R and its antagonists, since this receptor has been shown to have a novel pathophysiological role in brain damage [7].…”
Section: Discussionmentioning
confidence: 99%
“…CysLTs activate their corresponding receptors, such as the CysLT1 receptor (CysLT1R) and CysLT2 receptor [4], which mediate various responses in the peripheral and central nervous systems [5,6]. Moreover, CysLT1R is expressed in neurons and glial-appearing cells in brains after traumatic injury [7].…”
Section: Introductionmentioning
confidence: 99%
“…CysLTR-1 [26], whose expression is normally lower than the CysLTR-2 one [1, 3], is localized in microvascular endothelial cells [21], in glial cells, and in several types of neuronal cells [15, 27, 28]. …”
Section: Cerebral Localization Of Cyslt Receptorsmentioning
confidence: 99%